Development of a Fourier Transform-Based Gamelan Signal Processing Simulation Using Python and GNU Octave to Support Problem-Solving Skills and Independent Learning - Aditya Yoga Purnama; Fitria Sulistyowati; Widodo Widodo; Alfat Khaharsyah; Ragil Saputri; Rudolfus Soares; Radhiatul Amalia (South Sulawesi Education Development (SSED), 2026)
Science education today requires integrating technological competencies to prepare students for global competition; however, unsupportive learning habits and limited use of technology contribute to low levels of problem-solving skills and learning independence. This study aims to develop a simulation of gamelan musical instrument signal processing using open-source computational platforms, namely Python and GNU Octave. The research employed a research and development (R&D) approach based on the Borg and Gall model, limited to the initial product development stage. Fourier Transform analysis was applied to convert sound signals from the time domain into the frequency domain. The simulation successfully identified the gamelan’s natural frequency at 328 Hz via spectral analysis, with consistent results on both platforms. The developed simulation provides visualization of time-series waveforms and frequency spectra and is intended as a computational learning medium for physics instruction, particularly in wave topics. Although field testing and effectiveness evaluation were not conducted, the simulation is designed to support the development of students’ problem-solving skills and learning independence in future implementations.